Mental Well-Being During Pandemic: The Role of Cognitive Biases and Emotion Regulation Strategies in Risk Perception and Affective Response to COVID-19 - Schudy, Anna; Żurek, Karolina; Wiśniewska, Marcelina; Piejka, Aleksandra; Gawȩda, Łukasz; Okruszek, Łukasz (Frontiers in Psychiatry, 2020)
Both cognitive appraisals of risks associated with the specific disease and affective response to crisis situations have been shown to shape an individual response to pandemics. COVID-19 pandemic and measures introduced to contain it present an unparalleled challenge to mental well-being worldwide. Here, we examine the relationship between self-reported cognitive biases (CB) and emotion regulation skills (ER), COVID-19 risk perception and affective response, and mental well-being (MWB). 511 individuals completed General Health Questionnaire, Emotion Regulation Questionnaire, Davos Assessment of Cognitive Biases Scale (DACOBS) as well as scales measuring COVID-19 risk perception and affective response during the initial days of the epidemic in Poland. We used path and bootstrapping analyses to examine the hypothesis that CB may shape MWB during COVID-19 pandemic both directly and indirectly by (i) decreasing ER capacity and (ii) by increasing COVID-19 risk perception and affective response. Negative effect of CB and positive effect of ER via cognitive reappraisal on MWB were observed in participants. Furthermore, in line with our hypothesis, we observed indirect effects of CB via increased COVID-19 risk perception and affective response and decreased use of reappraisal strategy, which all, in turn, were related to MWB. Finally, we found an indirect effect of CB on MWB through double mediation of suppression strategies and COVID-19 affective response. Results of the current study suggest that CB, which have been shown to be linked to a variety of mental health symptoms in nonclinical populations, may exacerbate the impact of the COVID-19 pandemic on mental health outcomes.